2019
DOI: 10.1093/eurheartj/ehz851
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction treatments and outcomes in 6.5 million patients with a current or historical diagnosis of cancer in the USA

Abstract: Aims The aim of this study is to evaluate temporal trends, treatment, and clinical outcomes of patients who present with an acute myocardial infarction (AMI) and have a current or historical diagnosis of cancer, according to cancer type and presence of metastases. Methods and results Data from 6 563 255 patients presenting with an AMI between 2004 and 2014 from the US National Inpatient Sample (NIS) database were analysed. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(149 citation statements)
references
References 27 publications
7
128
1
Order By: Relevance
“…Cancer disease has been reported to be present in up to 17% of patients with ACS [ 3 , 4 , 7 , 8 ]. Very recent data from 6.5 million patients presenting with an acute myocardial infarction (AMI) between 2004 and 2014, included in the US National Inpatient Sample (NIS) database, showed a prevalence of 9% of patients with cancer [ 3 ].…”
Section: Prevalence and Clinical Characteristics Of Acs In Cancer mentioning
confidence: 99%
See 3 more Smart Citations
“…Cancer disease has been reported to be present in up to 17% of patients with ACS [ 3 , 4 , 7 , 8 ]. Very recent data from 6.5 million patients presenting with an acute myocardial infarction (AMI) between 2004 and 2014, included in the US National Inpatient Sample (NIS) database, showed a prevalence of 9% of patients with cancer [ 3 ].…”
Section: Prevalence and Clinical Characteristics Of Acs In Cancer mentioning
confidence: 99%
“…A very recent analysis on a large AMI population revealed that patients with current cancer have a 50% increased risk of major in-hospital adverse cardiac events than those without cancer [ 4 ]. Conversely, AMI patients with historical cancer were at no increased risk of adverse outcomes.…”
Section: Outcomes Of Cancer Patients With Acsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Patients with newly diagnosed cancer are at 2-to 3-fold greater risk of incident myocardial infarction or ischemic stroke compared with patients without cancer, 4 and those treated with radiotherapy have an absolute risk increase of 76.4 cases of coronary heart disease and 125.5 cases of cardiac death per 100,000 person-years. 5 It is therefore not surprising that physicians are increasingly encountering patients with cancer who have manifestations of coronary artery disease (CAD), either emergently in those presenting with acute coronary syndromes 6 or electively when myocardial revascularization in patients with severe CAD allows for subsequent safe surgical treatment of their cancer.…”
mentioning
confidence: 99%